Developmental Trajectories of Emotion Regulation Across Infancy: Do Age and the Social Partner Influence Temporal Patterns. (1st December 2012) - Ekas, Naomi V.; Lickenbrock, Diane M.; Braungart‐Rieker, Julia M.
<x xml:space="preserve">Abstract</x> The ability to effectively regulate emotions is a critical component of early socio‐emotional development. This longitudinal study examined the developmental trajectories of emotion regulation in a sample of 3‐, 5‐, and 7‐month‐olds during an interaction with mothers and fathers. Infants' negative affect and use of behavioral strategies, including distraction, self‐soothing, and high intensity motor behaviors were rated during the still‐face episode of the Still‐Face Paradigm. Longitudinal mixed‐effects models were tested to determine whether strategies were followed by an increase or decrease in negative affect. Results from mother‐infant and father‐infant dyads indicated that focusing attention away from the unresponsive parent and engaging in self‐soothing behaviors were associated with a subsequent decline in negative affect and the strength of these temporal associations were stable across infancy. In contrast, high‐intensity motor behaviors were followed by an increase in negative affect and this effect declined over time. No significant effects were found for the behavioral strategy of looking at the parent. Results underscore the importance of considering infant age and the social partner when studying the effectiveness of emotion regulatory strategies in early infancy.